LISTENING PROBLEMS IN PRIVATE COURSE - JESICA INSANI PURBA; APRIDA YANTI HUTAGALUNG; EVELIN TRINITA PAKPAHAN; PRATIWI SETIA BINA MANURUNG; SELVIANA NAPITUPULU (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
This article describes the English listening problems faced by private course students in Pematangsiantar. Specifically revealing (1) students' English listening skills, (2) problems faced in listening to English and (3) how teachers solve these problems. Data were obtained through a series of English listening tests using recordings with native and non-native speakers, observations and interviews. The findings show (1) the problems they often face in listening to English which are related to speaking speed, limited vocabulary, concentration levels and language habits, and (3) To overcome them, teachers must apply the correct technique of practice. by providing students with several ways to practice listening to English. Thus, it can be concluded that the teacher's efforts can solve problems by listening to the problems faced by students